Pemodelan Relai Diferensial Transformator Daya - Gusmelyana, Reska Anna; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The protection system identifies the disturbance that occurs and separates the affected part of the disorder from other parts that are working normally. The main protection equipment of the power transformer is a differential relay that works with the current balance method that is in accordance with the law of kirchoff current that is, the current that goes equal to the current leaving the branch point. The method used in this study is the collection of secondary data at Garuda Sakti Substation, as well as doing modeling and simulation with ETAP 16.0 software. From the simulation obtained the result that differential relay is inactive when there is an external interference in transformer 1 and transformer 3 due to differential relay work selectively. At the time of internal disturbance in transformer 1, Relay 1 at 2.0 ms feels the disturbance and works. The disruption resulted in relay 9 sending trip signals on CB1 and CB2 at 40 ms. At 42 ms CB1 and CB2 were active to disconnect the network. At the time of internal interference in transformer 3, then at 1.0 ms relay feels the disturbance so that the relay sends a trip signal on CB5 and CB6 at 40 ms. At 41 ms CB1 and CB2 time is active by sending trip signals to CB.Keywords : Protection System, Power Transformer, Differential Relay